Rift zone reorganization through flank instability in ocean island volcanoes: an example from Tenerife, Canary Islands - Walter T.R.; Troll V.R.; Cailleau B.; Belousov A.; Schmincke H.-U.; Amelung F.; v.d. Bogaard P. (My University, 2005)
The relationship between rift zones and flank instability in ocean island volcanoes is often inferred but rarely documented. Our field data, aerial image analysis, and 40 Ar/39 Ar chronology from Anaga basaltic shield volcano on Tenerife, Canary Islands, support a rift zone - flank instability relationship. A single rift zone dominated the early stage of the Anaga edifice (~6–4.5 Ma). Destabilization of the northern sector led to partial seaward collapse at about ~4.5 Ma, resulting in a giant landslide. The remnant highly fractured northern flank is part of the destabilized sector. A curved rift zone devel-oped within and around this unstable sector between 4.5 and 3.5 Ma. Induced by the dilatation of the curved rift, a further rift-arm developed to the south, generating a three-armed rift system. This evolutionary sequence is supported by elastic dislocation models that illustrate how a curved rift zone accelerates flank instability on one side of a rift, and facilitates dike intrusions on the opposite side. Our study demonstrates a feedback relationship between flank instability and intrusive development, a scenario probably common in ocean island volcanoes. We therefore propose that ocean island rift zones represent geologically unsteady structures that migrate and reorganize in response to volcano flank instability.
Keywords: Tenerife; Rift zone; Dike intrusion; Volcano flank instability; Constructive-destructive feedback mechanism; Canary Islands